Ocular repercussions in COVID-19 patients: structural changes of the retina and choroid - Poças, Ilda Maria (2022)
Purpose: In March 2022, after 1 year of the emergence of the pandemic by Covid-10 in Portugal, 3413013 positive cases were recorded. The eye can be not only the gateway for coronaviruses (CoV) but also one of their target organs. Conjunctivitis, uveitis, vasculitis, retinitis, and optic neuritis have been documented in animal models. Although most studies focus on respiratory tract involvement, ocular surface involvement such as tears are also reported in other CoVs and their relationship should be valued and studied as a form of treatment, contagion, and transmission. Also, the neurotropism of CoVs, not only through hematogenous dissemination but also through the retrograde neuronal route, associated or not with vascular/ischemic compromise of COVID-19 and its brain sequela may justify the use of non-invasive methodologies to characterize the retina and choroid of patients infected with COVID-19. The possible neurodegeneration associated with the coronavirus will be important to assess the thickness of the innermost layers of the upper hemiretin, with involvement described in other neurodegenerative diseases.